Not Automatic: Women and the Left in the Forging of the Auto Workers' Union - Wigderson, Seth (Labour / Le Travail, 2003)
The article reviews the book "Not Automatic: Women and the Left in the Forging of the Auto Workers' Union," by Sol Dollinger and Genora Johnson Dollinger.
Keywords: BOOKS -- Reviews; DOLLINGER, Genora Johnson; DOLLINGER, Sol; Labor Unions; NOT Automatic: Women & the Left in the Forging of the Auto Workers' Union (Book); Nonfiction